The relationship between financial intermediation development and poverty levels: An empirical analysis - Vladimirovich, Turyan Karen (International Journal of Innovative Research and Scientific Studies, 2025)
Financial intermediaries are an important part of the financial infrastructure of the country’s economy, which is aimed primarily at satisfying the needs of the population. Poverty, in a broad sense, is a condition incompatible with the satisfaction of all needs. Thus, financial intermediation, by its nature, carries a toolkit that prevents the spread of poverty. A poor person is not a consumer of financial services, which encourages intermediaries to improve the welfare of citizens to increase the demand for services. The dependence of the poverty level on the development of financial intermediation is of high importance for addressing the challenges faced by developing economies. The purpose of this research is to study the directions of the relationship between the development of mediation and the level of poverty based on an empirical analysis of data on the development of the economies of post-Soviet countries. The author substantiated the need to combine private and public efforts in solving the problems of developing financial intermediation and reducing poverty. It is necessary to maintain a balance of individual and public interests when developing a policy for the development of financial intermediaries.